Response of different bean genotypes to soil nutrients and water in the semi-arid areas of eastern Kenya (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
Beans (Phaseolus vulgaris L.) are important legumes in the semi-arid areas of Eastern Kenya. But their production is constrained by water stress within the season and between seasons. A field trial was conducted in the short rains in the year 2011 (October to December) and long rains of 2012 (March to June) at KARI-Katumani (10 35'S and 37014'E, and 1560 metres above mean sea level) to determine the effect of on soil moisture and soil nutrients on grain yield of three market -preferred bean genotypes; namely: Katumani bean 1, NUA 1 and NUA 4. The experiment was conducted using a randomized block design with three replications with treatments in split plot arrangement. Results showed that bean grain yields of Kat B1 and NUA1 grown on tied ridges with manure at 5 tons ha-1 produced significantly (P